Systemic Reform in a Federated System:Los Angeles at the Turn of the Millennium - Menefee-Libey, David (Education Policy Analysis Archives, 2004)
I synthesize some of the lessons we have learned about systemic school reform in order and derive two explicit hypotheses about when such reforms are likely to be more and less successful. The first hypothesis focuses on program implementation: to achieve success, any systemic reform must overcome challenges at each stage of the policy-making process, from agenda-setting to policy choice to implementation. The second hypothesis focuses on the federated nature of education policymaking in the United States: any successful systemic reform must offer a program that aligns local efforts with state and sometimes federal policy. I derive and test more specific hypotheses related to recent systemic reform efforts in the Los Angeles region—especially the Los Angeles Annenberg Metropolitan Project, or LAAMP—which ran from 1995 through 2001. The case confirms the hypotheses and enables a clearer understanding of systemic school reform.